English Communication Strategies of the Students Semester V (Year 2011) at English Department in FKIP UHN Pematangsiantar - Bertaria Sohnata Hutauruk (Journal of English Language and Culture, 2017)
Communication Strategies are ways of the learners to explain a message to his listener when the initial plan cannot be carried out. In this research, the problem of the research is as follow: “what communication strategies are used by the students on the fifth semester (year III) in learning English at English Department at FKIP UHN Pematangsiantar? To solve the problem above, the writer used the theory of Ellis (1985), Faerch and Kasper in Ellis (1985), and Brown (1980). The limitation of this research is on classroom realities in learning English as a foreign language. The subject of this research is the students on the fifth semester (year III) in learning English at English Department at FKIP UHN Pematangsiantar. The data are interpreted by using theory by Faerch and Kasper about types of communication strategies. The data analysis shows that the students on the fifth semester (year III) who learn English at English Department at FKIP UHN Pematangsiantar used some types of communication strategies in communication one to another when they have problem how to say or to express a message to their listener in target language. The data analysis shows that the students used formal reduction strategies, foreignizing strategies, code-switching strategies and indirect appeal strategies. However, the analysis shows that the students used formal reduction strategies more often than other strategies. The writer concludes that communication strategies are very important for learning English as a foreign language. The best strategy users are those with adequate formal proficiency who modify the strategy to suit the specific concept to be conveyed. Therefore, the writer suggests when learners have to refer to some object without knowing the second language word, they can use the communication strategies so that the can keep the conversation. Keywords: communication, strategies, learning